Implementasi Manajemen Perubahan Dalam Sistem Informasi - Septiana, Ria; Aslami, Nuri (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2023)
The results of this study are expected to provide a better understanding of how the implementation of change management can affect the success of information systems implementation. This article can provide valuable insights for organizations that are currently or will be adopting a new information system, so that they can identify and control the risks that may arise during the implementation process. Information systems require processes and stages that are many and interrelated with one another. The process of implementing an information system can also have an impact on changes that need attention. The successful implementation of information systems in an organization is influenced by how change is managed. Therefore, it is important to have guidelines governing change management in order to manage changes that occur during the information system implementation process.